Evaluation of blood flow on optic nerve head after pattern scan and conventional laser panretinal photocoagulation - Iwase, Takeshi (Medicine (Baltimore), 2019)
To evaluate the changes in the blood flow on retina and the optic nerve head (ONH) after conventional laser treatment and to compare it to that after patterned scanning laser (PASCAL) treatment in patients with severe nonproliferative diabetic retinopathy (S-NPDR). In this prospective, cross-sectional study, the blood flow on retina and the ONH was assessed by laser speckle flowgraphy using the mean blur rate (MBR) in 39 eyes with S-NPDR before, 1, 4, 8, 12 weeks after panretinal photocoagulation (PRP). Of 39 eyes, 17eyes with 17 patients treated by conventional laser and 22 eyes with 22 patients treated by PASCAL. The mean age was 55.5 ± 11.5 years in the conventional laser group, 55.6 ± 11.8 years in the PASCAL group. The MBR-vessel, which can be dominantly expressed as retinal blood flow, was significantly reduced after PRP treated by conventional laser (P < .001), but did not change after PRP treated by PASCAL. The ratio of MBR-vessel to the baseline was significantly lower in the conventional laser group only at Week 1 (P = .045). The MBR-tissue, which can be dominantly expressed as the ONH blood flow, did not significantly change after PRP in the both group. The multiple stepwise regression analysis revealed that the laser burns was an independent factor significantly correlated with the ratio of MBR-vessel at Week 1 to the baseline (β = −0.550, P = .012). The retinal blood flow was significantly reduced during the 12 weeks only after completion of PRP by conventional laser treatment. Our results indicate that short pulse on PRP treatment performed by the PASCAL would not significantly reduce the retinal blood flow.